Innovation of Jempol HAM Services (Human Rights Based Football Pick Up) in Making Passports at the TPI Pekanbaru Class I Immigration Office - Fadhil Afriliansyah; Dadang Mashur (Journal of Education Technology Information Social Sciences and Health, 2024)
Public service providers are always required to innovate in improving the quality of public services, therefore the TPI Pekanbaru Class I Immigration Office has created a Jempol HAM Service Innovation (Human Rights-based pick-up and drop-off) for people who want to make a passport and cannot come directly to the office TPI Pekanbaru Class I Immigration. This research aims to determine the Innovation of Thumb Human Rights Services in Making Passports at the TPI Pekanbaru Class 1 Immigration Office and the purpose of the Thumb Human Rights Service Innovation is aimed primarily at vulnerable groups such as emergency, disabled and elderly over 65 years who cannot come directly to the TPI Class I Immigration office In Pekanbaru, the Jempol HAM service innovation emerged. The concept used is the concept of innovation according to Widodo, namely that innovation must be sustainable, have a positive impact on society and be able to provide solutions to problems. The type of research used is qualitative with a phenomenological approach. The results of this research are that innovation has gone as well as possible and the public hopes that this innovation will continue in the future, but problems are still found such as a lack of human resources because there are no special staff in the field of human rights issues and a lack of supporting facilities in carrying out human rights innovations. and lack of coordination with the hospital to implement these thumb human rights services.